BIOM-38. TETRASPANIN 12 AS A TUMOR SUPPRESSOR AND BIOMARKER PREDICTING GOOD PROGNOSIS OF MALIGNANT GLIOMA. (14th November 2022) - Lee, Yeo Song; Kim, Chungyeul; Choi, Hye Won; Lee, Jungsul; Jung, Hyena; Suh, Sangil; Kim, Hyungsin; Kang, Shin-Hyuk; Kwon, Taek-Hyun; Chong, Kyuha
Abstract: Tetraspanin 12 (TSPAN12), a member of the tetraspanin family that are increasingly known to be involved in various mechanisms of tumor progression, mediates various cellular signaling processes in cancer cells. With respect to the brain, previous studies have shown that TSPAN12 is related with the maturation of a membrane-associated metalloproteinase 10 and the production of amyloid β plaque, but there are no studies related to brain tumors to date. Therefore, we designed this study to investigate the role of TSPAN 12 on malignant glioma (MG) cells and patients. TSPAN12 silencing in MG cells significantly progressed cell proliferation, migration and invasion capacities, and extracellular matrix adhesion ability as well as stem cell properties, in vitro . Mechanistically, we identified that FAK and ERK signaling were involved in MG cells with TSPAN12 expression. Moreover, clinical analysis of MG patient tissues microarray showed that the expression level of TSPAN12 was negatively correlated with the prognosis in MG patients. Collectively, more studies are needed, but we suggest that TSPAN12 can be used as an alternative biomarker to predict the prognosis of MG patient and help develop MG treatment strategies.